1999
DOI: 10.1097/00005072-199908000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Intracellular Amyloid-β Peptide (Aβ 1–40) in Mucopolysaccharidosis Brains

Abstract: To evaluate whether in vivo accumulations of heparan sulfate caused by inborn errors in the metabolism of glycosaminoglycans lead to the formation of neurofibrillary tangles and/or senile plaques, as seen in Alzheimer disease (AD), we studied postmortem brains from 9 patients, ages 1 to 42 years, with mucopolysaccharidosis (MPS). The brains of patients with Hurler's syndrome (MPS I: n = 5) and Sanfilippo's syndrome (MPS III; n = 4) as well as from caprine MPS IIID and murine MPS VII models were evaluated by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 0 publications
2
35
0
Order By: Relevance
“…Others have looked for but did not find hyperphosphorylated tau in brain of human MPS patients or animal models (26,27). From our experience with the MPS III B mouse model, we believe that hyperphosphorylated tau can be easily missed.…”
Section: Discussionmentioning
confidence: 78%
“…Others have looked for but did not find hyperphosphorylated tau in brain of human MPS patients or animal models (26,27). From our experience with the MPS III B mouse model, we believe that hyperphosphorylated tau can be easily missed.…”
Section: Discussionmentioning
confidence: 78%
“…1,3 While detailed mechanisms of pathology, especially the neuropathology of MPS III, are not yet well understood, numerous studies have reported cascades of complex secondary pathological events in the CNS, including broad metabolic impairments, [4][5][6] neuroinflammation, 5,7-11 oxidative stress, 10,12 autophagy, 13,14 and neurodegeneration. 7,9,11,[15][16][17][18][19][20] It is worth noting that many of these secondary neuropathological features of MPS IIIB, such as b-amyloid (Ab) aggregation, 15,18 tauopathy, 17,18 synucleinopathy, 16,19 oxidative stress, 10,12 and neuroimflammation, 5,[7][8][9][10][11] are also common hallmarks of other neurodegenerative diseases like Alzheimer's (AD) 21,22 and Parkinson's disease (PD). 23,24 In addition, our recent studies demonstrate widespread profound neuropathology in the peripheral nervous system (PNS), 25 indicating that neuropathological manifestation affects the entire nervous system.…”
Section: Mucopolysaccharidosis (Mps) Iiib (Online Mendelian Inheritanmentioning
confidence: 99%
“…34,35 H&E was performed using undiluted hematoxylin (Gill's #2; Electron Microscopy Sciences, Fort Washington, PA, USA) followed by immersion in a working solution of 0.3% eosin. 5,36 For AO staining, tissue sections were placed in a 0.2 M dibasic sodium phosphate/0.1 M citric acid (SC; pH 4.0) solution for 5 min prior to staining with AO (10 mg/ ml) in SC buffer for 15 min. The sections were rinsed three times in SC buffer and immersed briefly in 50% ethanol in 0.1 M Tris.…”
Section: Histochemical and Immunocytochemical Preparationmentioning
confidence: 99%